2020
DOI: 10.18203/2394-6040.ijcmph20204369
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices regarding management of minor ailments of pregnancy among antenatal mothers: a descriptive study from Rajasthan

Abstract: Background: Pregnancy is considered as one of the most beautiful events in every female life which brings a lot of physiological and hormonal changes to prepare women for motherhood. Even though these changes are not dangerous, still they are bothersome. Women use number of homemade remedies to alleviate these discomforts. Objective: The objective of this study was to assess knowledge and practices regarding management of minor ailments of pregnancy among antenatal mothers.Methods: This study was conducted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…In the present study, the awareness level had significant association with type of family (p = 0.017).The finding is consistent with the findings of similar study done in India where there was significant association between level of awareness of pregnant women and type of family 6 .This finding contradicts to the study conducted in Sri Lanka where the knowledge level had significant association with religion (p <0.001), ethnicity (p=0.013), monthly income (p <0.001) and educational level (p <0.001) 2 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the awareness level had significant association with type of family (p = 0.017).The finding is consistent with the findings of similar study done in India where there was significant association between level of awareness of pregnant women and type of family 6 .This finding contradicts to the study conducted in Sri Lanka where the knowledge level had significant association with religion (p <0.001), ethnicity (p=0.013), monthly income (p <0.001) and educational level (p <0.001) 2 .…”
Section: Discussionsupporting
confidence: 92%
“…A study of India showed that 94% pregnant women had urinary frequency, 83.7% had nausea and vomiting, 82.6% had backache, 75% had heart burn, 73.4% had leg cramps, 71.7% had insomnia, 56.2% had constipation. 6 A study done in Kaski, Nepal showed that 24.3% pregnant women suffered from backache followed by nausea & vomiting and heart burn. 7 A study from India showed that 87% of antenatal mothers have inadequate level of knowledge regarding minor disorders of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Other common symptoms were backache (152, 32.6%), dizziness (112, 24.0%) and heartburn/regurgitation (107, 23.0%). The leading cause of hospitalization was NVP which accounted for 43.1% of total admissions during pregnancy [6] Sharma, Ankita et al (2020) [7] discovered that increased urine frequency is the most evident minor complaint faced during pregnancy. Overall antenatal mothers had fair knowledge regarding management of minor ailments and varied practices have been performed by antenatal mothers to relieve their problems.…”
Section: ~ 2 ~mentioning
confidence: 99%
“…Overall antenatal mothers had fair knowledge regarding management of minor ailments and varied practices have been performed by antenatal mothers to relieve their problems. [7] Marie Rosy (2014) [8] found that, 87% of antenatal mothers have inadequate level of knowledge and 65% of them had inadequate practices regarding minor disorders of pregnancy. Study also found that there was high correlation between knowledge and practice scores of minor disorders of pregnancy.…”
Section: ~ 2 ~mentioning
confidence: 99%
“…regnancy is a period in which a woman carries a developing fetus [1]. It consists of three trimesters marked by specific foetal developments [2]. Pregnancy is accompanied by certain physiological and psychological changes that can be stressful for pregnant women [3].…”
Section: Introductionmentioning
confidence: 99%